2018
DOI: 10.1016/j.ejmech.2018.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of 1,2-dione-containing abietane analogues for the generation of human carboxylesterase inhibitors

Abstract: Recently, a series of selective human carboxylesterase inhibitors have been identified based upon the tanshinones, with biologically active molecules containing a 1,2-dione group as part of a naphthoquinone core. Unfortunately, the synthesis of such compounds is complex. Here we describe a novel method for the generation of 1,2-dione containing diterpenoids using a unified approach, by which boronic acids are joined to vinyl bromo-cyclohexene derivatives via Suzuki coupling, followed by electrocyclization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…There are two major isoforms of hCEs identified in humans, such as carboxylesterase 1 (hCE1) and carboxylesterase 2 (hCE2). They display a notable difference in tissue distribution and substrate preference. , In addition to modulating lipid/glucose homeostasis, hCEs also participate in the activation of anticancer entities such as irinotecan and gemcitabine. ,,, Current reported inhibitors against hCEs encompass natural compounds like fatty acids, flavonoids, tanshinones, and triterpenoids and synthetic compounds like bisbenzene sulfonamides, 1,2-diones, trifluoroketones, carbamates, etc. Among them, only the 1,2-dione moiety is well-elucidated as the classical functional group through covalently modifying the key serine residue in the catalytic center of hCEs .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…There are two major isoforms of hCEs identified in humans, such as carboxylesterase 1 (hCE1) and carboxylesterase 2 (hCE2). They display a notable difference in tissue distribution and substrate preference. , In addition to modulating lipid/glucose homeostasis, hCEs also participate in the activation of anticancer entities such as irinotecan and gemcitabine. ,,, Current reported inhibitors against hCEs encompass natural compounds like fatty acids, flavonoids, tanshinones, and triterpenoids and synthetic compounds like bisbenzene sulfonamides, 1,2-diones, trifluoroketones, carbamates, etc. Among them, only the 1,2-dione moiety is well-elucidated as the classical functional group through covalently modifying the key serine residue in the catalytic center of hCEs .…”
Section: Resultsmentioning
confidence: 95%
“…Previously reported studies have confirmed the significance of Ser221 and His468 in the hCE1 reaction, of which the former residue is the nucleophilic attack center toward substrates. ,, We sampled the distribution of key distance involved in the initial hydrolysis reaction. As shown in Figure D, the distance from OSer221 to CLigand (Dis-OSer221_CLigand) corresponding to the nucleophilic attack process has the same distribution pattern for both systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation of phenols and naphthols by IBX to 1,2-quinones is a well-known reaction . The chemistry of 1,2-quinones has been immensely investigated in the literature .…”
Section: Resultsmentioning
confidence: 99%
“…Another approach is that miltirone and bidwillon A, as prototypes of natural origin, should be used for chemical modification and structure–activity relationship (SAR) studies to improve its P-gp-inhibiting properties and to drive forward the development of clinical candidates. Miltirone derivatives have been synthesized in the past and subjected to SAR studies in different contexts [ 75 , 76 , 77 ]. These studies may be taken as a proof-of-principle that at least miltirone is in general suitable for derivatization and SAR studies.…”
Section: Discussionmentioning
confidence: 99%